PRAKTIK ILLEGAL FISHING DI PERAIRAN INDONESIA SEBAGAI TRANSNATIONAL ORGANIZED CRIME (STUDI KASUS KAPAL RUN ZENG DI LAUT ARAFURA) - Tampubolon, Bona Jevon; Raden Roro Kamilia Hana Putri; Abqary Faraz Darmawan (Jurnal Hukum Statuta, 2024)
As one of the largest archipelagic countries in the world with a larger marine area than its land, Indonesia has abundant potential for marine resources. For example, the Arafura Sea has the highest fisheries potential compared to other Indonesian waters. However, this also increases the potential for fisheries crimes that threaten the security of Indonesian waters, such as illegal fishing. The method used in this research is juridical-normative, or what is commonly called doctrinal legal research with case studies to be analyzed. This research also uses a statute approach and historical approach. The results obtained from this research are that the practice of illegal fishing is classified as a transnational organized crime, and analysis is carried out on cases that occur in the Arafura Sea as a real example. The practice of illegal fishing is regulated through UNCLOS, which is the international legal basis for marine management. This practice has significant implications, not only on the economy but also the sustainability of Indonesia's marine ecosystem. Enforcement is carried out through the sinking and burning of foreign vessels proven to have violated the law and the establishment of Task Force 115 as an effort to deal with illegal fishing. In addition, international collaboration and cooperation between countries is needed to minimize the practice of illegal fishing.